PERAN NORMA HUKUM DALAM MENATA KEGIATAN EKONOMI NASIONAL MENUJU DISTRIBUSI KEKAYAAN YANG ADIL: TINJAUAN LITERATUR ATAS IMPLEMENTASI ASAS KEADILAN SOSIAL DAN KEDAULATAN EKONOMI RAKYAT DI INDONESIA - Gunawan Widjaja (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
This study analyses the role of legal norms as the main constitutional instrument in regulating Indonesia's national economic activities towards a fair distribution of wealth through a normative-juridical literature review of the implementation of the principles of social justice (the fifth principle of Pancasila) and economic sovereignty of the people (Article 33 of the 1945 Constitution), where findings show that although derivative regulations such as the State-Owned Enterprises Law, the Job Creation Law, and redistributive policies (KUR, Village Funds, agrarian reform) have attempted to implement the principles of familial economic democracy, a significant gap still exists due to the dominance of neoliberalism, weak institutional enforcement, and structural inequality with a Gini ratio of 0.375. An analysis of two main discussions reveals that legal norms are effective as national economic governance through state control of strategic production sectors and synergy between state-owned enterprises and micro, small and medium enterprises (MSMEs). but the implementation of the principle of social justice is hampered by poor inter-agency coordination and systemic corruption, where Rawls' perspective on the difference principle reinforces the recommendation for progressive regulatory reform to ensure that economic benefits flow to the most disadvantaged groups. Thus, the conclusion emphasises the need to harmonise ius constitutum and ius operatum through the strengthening of the Constitutional Court's judicial review, revising the inclusive Job Creation Law, and developing social welfare-oriented SOE holdings to realise a distributively just Indonesia Emas 2045, with theoretical implications for the development of the Pancasila economic law doctrine and practical implications for policymakers in reducing urban-rural disparities.